Short Communication: Isolation and characterization of thermophilic actinobacteria as proteolytic enzyme producer from Ie Seuum Hot Spring, Aceh Besar, Indonesia - Lenni Fitri; KARTINI AMELIA PUTRI; SUHARTONO; YULIA SARI ISMAIL (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Fitri L, Putri KA, Suhartono, Ismail YS. 2019. Short Communication: Isolation and characterization of thermophilic actinobacteria as proteolytic enzyme producer from Ie Seuum Hot Spring, Aceh Besar, Indonesia. Biodiversitas 20: 2802-2808. Proteases are enzymes who catalyze the breakdown of peptide bonds in proteins. This enzyme could be produced from thermophilic bacteria that are able to grow at temperatures of 45-80ºC and are stable to heat. The samples were collected at Ie Seu'um hot spring, Aceh Besar. This study aimed to isolate, to characterize and to determine actinobacteria that were capable of producing protease enzymes. The sampling method in this study was conducted by purposive sampling at temperatures of 50, 60 and 70ºC. Isolation of thermophilic actinobacteria was carried out in Humic Acid Vitamin B (HV) Agar medium and morphological characterization was carried out in Yeast Malt Agar (YMA), Yeast Starch Agar (YSA), Oatmeal Agar (OA) media. Microscopic characterization and measurement of clear zone diameter formed were carried out in skim milk medium. The results showed that one actinobacteria isolate was obtained at a temperature of 50ºC and five isolates at a temperature of 60ºC, meanwhile, no actinobacteria could be obtained at a temperature of 70ºC. A total of 4 isolates obtained were able to produce protease enzymes. The highest Proteolytic Index (IP) value was obtained from IS01 which was 3.8.